The Czech Rhino Connection: a Case Study of Vietnamese Wildlife Trafficking Networks’ Operations Across Central Europe - Nožina, Miroslav (European journal on criminal policy and research, 2021)
This article focuses on the trafficking segment of the illegal wildlife market, or more specifically on organised trafficking in rhino horns from South Africa to Vietnam via the Czech Republic. Composed as a criminological case study, the article analyses how the wildlife trafficking networks were established by Vietnamese nationals in cooperation with providers in Africa and Central Europe, how they operate by crossing national borders and ethnic barriers, and how the illegal wildlife trade is incorporated into the Vietnamese criminal activities in Central Europe. Two important cases of rhino “pseudo-hunting” that were investigated by the Czech security forces, Operation Rhino and Operation Osseus, are discussed in this context.